Epidemiology, genetic diversity and evolution of canine astrovirus. Issue 6 (6th July 2020) - Zhang, Wenyan; Wang, Ruyi; Liang, Jiawei; Zhao, Naiyu; Li, Gairu; Gao, Qi; Su, Shuo
Abstract: Astroviruses (AstVs) are major causative agents of gastroenteritis in children and have been reported in many species. Canine astrovirus (CaAstV), as an enteric pathogen, has been widely detected worldwide, but little is known about their genetic diversity and evolution, partly owing to a lack of genomic data. Here, we sequenced 12 nearly full‐length CaAstV genomes to address the gap in knowledge. We found 14 (13.2%) and 7 (3.35%) CaAstV‐positive samples from pet dogs with and without diarrhoea, respectively. Co‐infections were with co‐infection with Torque teno canis virus (TTCaV) reported for the first time. Phylogenetic analysis of the ORF2 gene revealed four major lineages. In particular, lineage 4 might have evolved from a recombinant virus from lineage 2 and lineage 3. The strains sequenced here clustered with lineages 2, 3 and 4 in contrast with other Chinese strains identified previously that clustered with lineages 2 and 4. Amino acid sequence alignment within lineage revealed intralineage amino acid diversity and that the type of epidemic strains within lineages changes over time. Three amino acids substitutions located in predicted B‐cell epitopes, which might be involved escape of host immunity. Moreover, frequent inter‐clade ORF2 gene recombinants were identified. The identification of individual recombination events and a recombinant lineage indicated that recombination plays a crucial role in CaAstV genetic evolution and diversity by generating divergent viruses. Moreover, phylogenetic analysis of ORF1b, the most conserved gene of astrovirus, revealed a close relationship between CaAstV and California sea lion astroviruses. Overall, we report detailed information on the genetic evolution and diversity of CaAstV, which indicates that CaAstV may pose challenges for diagnostics and future control strategies.